Approach for enhancing mycorrhiza - mediated disease resistance of tomato damping-off - and A. SREEVANI, B.N. REDDY*, C.R. RAGHAVENDER (Indian Phytopathology, 2006)
The Arbuscular-Mycorrhizal (AM) fungus, Glomus fasciculatum was exploited in the present study for the control of damping-off disease in tomato seedlings caused by the pathogenic fungus, Pythium aphanidermatum. The results of the disease resistance parameters indicate that dual inoculations (AM + Pathogen) were significantly restricted the progression of the pathogen in the root tissues of both the genotypes of tomatoes tested (PED + Arkavikas). Mycorrhizal inoculations not only reduced the percentage of disease incidence but also the fruit yield and fruit weight. They AM association significantly increased the host plant height, total biomass and dry matter. It is clear from the study that inoculation of plants with AM fungi will improve plant health by enhancing nutrient status, yield and also by protecting the host plants against pathogens. It is difficult to generalize the interaction of pathogen-host-mycorrhiza but effective AM fungus can be used in controlling disease biologically. Exploitation of mycorrhizal fungi in commercial agriculture is possible only when the mycorrhizal inoculum is produced in large quantities and appropriate strategies are adopted for successful application of inoculum under field conditions.